Unions, temporary employment and hours of work: a tale of two countries - Marco Francesconi; Carlos Garcia-Serrano (University of Essex, Institute for Social and Economic Research (ISER), 2002)
This paper is the first attempt to analyse the relationship between unionisation, temporary employment and non-standard hours of work, comparing Spain and Britain, which are characterised by relatively different labour market structures and substantially different degrees of employment protections. Despite such differences, these two countries show remarkably similar responses of unionisation to flexible employment. In particular, we find that union recognition in Britain and firm-level union presence in Spain do not respond to changes in long hours of work, overtime hours and temporary employment, whereas part-time employment is negatively correlated with union recognition in both countries. We find, however, some important differences between the two countries when the samples are stratified by industry. In Britain, the negative correlation between union coverage and part-time employment is especially marked for workers in the service industries. In Spain, instead, most of the action involves firms in manufacturing and other industries. These different responses of unionisation to flexible employment may be the result of the different industrial structures which characterise the two economies. But they may also reflect the different way in which trade unions operate within each labour market.
Keywords: 330